Acetyl-11-keto-β-boswellic acid alleviates hepatic metabolic dysfunction by inhibiting MGLL activity - Kai Luan; Yuhong Fan; Qin Yang; Hailong Yang; Zelin Zhou; Ju Huang; Zhigang She; Toujun Zou; Hui Xiong; Zhinan Mei (Journal of Lipid Research)
Metabolic abnormalities have emerged as a central pathogenesis in various metabolic diseases, particularly nonalcoholic fatty liver disease (NAFLD) and its associated complications of obesity and insulin resistance. Despite this, effective pharmaceutical treatments for NAFLD-related metabolic disorders remain limited. In this study, we identified acetyl-11-keto-beta-boswellic acid (AKBA), a natural compound isolated from the gum resin of Boswellia carterii, showing robust capacity against NAFLD as well as its related body weight gain and insulin resistance. Our findings demonstrate that the beneficial effects of AKBA on metabolic disorders are largely dependent on its direct interaction with monoacylglycerol lipase (MGLL) in hepatocytes. In vivo experiments using a high-fat and high-cholesterol (HFHC) diet-induced NAFLD mouse model revealed that AKBA effectively mitigated both the progression of NAFLD and associated metabolic dysfunctions. Proteomic and RNA sequencing analyses further elucidated that AKBA attenuates key pathways related to lipid accumulation, inflammation, and fibrosis. Mechanistically, AKBA was found to directly target MGLL in hepatocytes, inhibiting its activity in hydrolyzing monoacylglycerols. Structural analyses revealed that AKBA binds specifically to the GLU60, MET64, THR279, and PHE283 residues of MGLL. Importantly, AKBA showed no additional therapeutic effect in MGLL-deficient models, underscoring the crucial role of MGLL in mediating AKBA's therapeutic action. In conclusion, our study identifies AKBA as a novel and potent MGLL inhibitor and suggests that it holds promise as a therapeutic candidate for NAFLD and related metabolic diseases. This research highlights the potential of natural compounds in the development of targeted treatments for metabolic disorders.